Effects of supplementation frequency on the ruminal fermentation and enteric methane production of beef cattle grazing in tropical pastures - Canesin, Roberta Carrilho [UNESP]; Berchielli, Telma Teresinha [UNESP]; Messana, Juliana Duarte [UNESP]; Baldi, Fernando [UNESP]; Pires, Alexandre Vaz; Shiraishi Frighetto, Rosa Toyoko; Fiorentini, Giovani [UNESP]; Reis, Ricardo Andrade [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2014)
The objective of this study was to evaluate the characteristics of ruminal fermentation and enteric methane production in beef cattle subjected to different supplementation frequencies while grazing on Brachiaria brizantha cv. Marandu pastures. Nine cattle (325 +/- 65.7 kg BW) fitted with ruminal and duodenal cannulas were used in the ruminal fermentation study, and 12 cattle (399 +/- 32.6 kg BW) were used in the enteric methane production study. The treatments included supplementation once daily, supplementation once daily except Saturdays and Sundays, or supplementation on alternate days. The supplementation was equivalent to 10 g kg(-1) BW day(-1) for all treatments. The design employed was completely randomized with three treatments and three replications. When all supplements were provided (day 1), no effects of supplementation frequency were observed on ruminal pH; concentration of NH3-N; concentration of acetic, propionic, or butyric acids; or total volatile fatty acids (VFA), but there were month effects. During the day on which only daily supplements were provided (day 2), significant differences were observed only on the molar concentration of acetic acid and total VFA; and month effects were noted on all variables. No significant differences were observed in ruminal fluid volume, dilution rate, N intake, bacterial N synthesis and enteric methane production among the studied supplementation frequencies. Differences were observed in the enteric methane production in the different months, with 85 g kg(-1) of gross energy intake observed in September and 123 g kg(-1) of gross energy intake observed in November. Lower supplementation frequency is a good option to lower labor costs with little or no consequences on ruminal fermentation characteristics and enteric methane production.
Keywords: Bacterial N synthesis; N-alkane; Nutrient intake; Ruminal methane; Tropical pasture; Volatile fatty acids